Macronutrient intake inadequacy and associated factors among school adolescent girls in Meshenti, Northwest Ethiopia, 2020: 24-h recall - Birtukan Gizachew Ayal; Yeshalem Mulugeta Demilew; Hunegnaw Almaw Derseh (Public Health Nutrition)
Abstract